2003
DOI: 10.1038/sj.eye.6700313
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of 0.75% levobupivacaine vs 0.75% bupivacaine for peribulbar anaesthesia

Abstract: Background/aims Levobupivacaine, the S(-)-enantiomer of racemic bupivacaine, is associated with a similar efficacy but a reduced potential for cardiovascular and central nervous system toxicity than racemic bupivacaine. Thus, this prospective, randomised, double-masked study was undertaken to assess the efficacy and safety of 0.75% levobupivacaine vs 0.75% bupivacaine, each with hyaluronidase, for peribulbar anaesthesia. Methods A total of 60 patients undergoing elective anterior segment surgery were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
9
1
2
Order By: Relevance
“…Similar results were reported for retrobulbar and PBs when comparing different concentrations of levobupivacaine to bupivacaine 1215. Some patients experienced mild pain during the injection of local anesthetic but trivial pain was reported at the end of the procedure and before discharge.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar results were reported for retrobulbar and PBs when comparing different concentrations of levobupivacaine to bupivacaine 1215. Some patients experienced mild pain during the injection of local anesthetic but trivial pain was reported at the end of the procedure and before discharge.…”
Section: Discussionsupporting
confidence: 80%
“…However, Lai et al 13. found that a mixture of bupivacaine 0.75% and lidocaine 2% provided better akinesia than a mixture of levobupivacaine 0.75% and lidocaine 2% but in our study akinesia at 10 min did not differ from previous studies that used longer needles for injection 812. Hence anterior injection of anesthetics improves safety without decreasing the block quality 14…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In der oph thal mo lo gi schen An äs the sie wur den mit 0,75igem Le vo bu pi va cain in 3 Ar bei ten kei ne Un ter schie de zu Bu piva cain [83,84,85] oder Ro pi va cain [85] ge se hen; in ei ner Stu die wur den schlechte re Ope ra ti ons be din gun gen be ob ach tet [86]. In der Zahn-Mund-Kie fer-(ZMK-)An äs the sie zeig te Le vo bu pi va cain Vor teile ge gen über Li do cain und Pla ce bo [87] und war ver gleich bar mit Bu pi va cain [88].…”
Section: An De Re Kli Ni Sche An Wen Dun Genunclassified
“…A bupivacaína tem longa duração, possui efeito anestésico e analgésico, o início de sua ação anestésica varia entre 2 a 10 minutos e seu efeito pode durar até 7 horas em alguns pacientes, o que é aproximadamente 3x mais tempo que a lidocaína. A bupivacaína racêmica tem se mostrado eficaz para o bloqueio peribulbar (4) e sua principal desvantagem está relacionada à cardiotoxicidade (5,6) . A lidocaína é um fármaco de curta ação, com iní-cio de ação em 1 a 5 minutos após infiltração e em 5 a 15 minutos para outras vias de administração.…”
Section: Introductionunclassified